http://isrctn.com/ 2017
DOI: 10.1186/isrctn33469250
|View full text |Cite
|
Sign up to set email alerts
|

Implant stability in the posterior maxilla: a controlled clinical trial

Abstract: Aim. To evaluate the primary and secondary stability of implants in the posterior maxilla. Methods. Patients were allocated into three groups: (A) native bone, (B) partially regenerated bone, and (C) nearly totally regenerated bone. Insertion torque (IT) and implant stability quotient (ISQ) were measured at placement, to evaluate whether satisfactory high primary stability (IT ≥ 45 N/cm; ISQ ≥ 60) was achieved; ISQ was measured 15, 30, 45, and 60 days after placement, to investigate the evolution to secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Our data demonstrated a general linear relationship between insertion torque and implant stability: the strength of this correlation resulted statistically significant for the entire sample ( p = 0.0001), in accordance with a recent study by Zita Gomes et al [ 46 ] on tapered implants with knife-edge thread design placed in the posterior maxilla. However, at a deeper analysis, the linear relationship between insertion torque and implant stability is valid only in the medium torque group (30 < IT < 50 N/cm) ( p = 0.015), while it was not significant in low and high torque groups ( p = 0.094 and p = 0.565, resp.).…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrated a general linear relationship between insertion torque and implant stability: the strength of this correlation resulted statistically significant for the entire sample ( p = 0.0001), in accordance with a recent study by Zita Gomes et al [ 46 ] on tapered implants with knife-edge thread design placed in the posterior maxilla. However, at a deeper analysis, the linear relationship between insertion torque and implant stability is valid only in the medium torque group (30 < IT < 50 N/cm) ( p = 0.015), while it was not significant in low and high torque groups ( p = 0.094 and p = 0.565, resp.).…”
Section: Discussionsupporting
confidence: 92%
“…Ti is one of the best materials for manufacturing dental implants because of its desirable biocompatibility and mechanical strength. Despite various benefits of Ti implants, it may lead to implantation failure because it could promote fibrous tissue development 131,132 . It was reported that coating Ti implants with GO (1.5 mg/ml) improves biocompatibility as well as proliferation and osteogenic differentiation of cells 132 .…”
Section: Graphene‐based Nanocomposites For Tissue Engineering Applica...mentioning
confidence: 99%